Peran Disiplin Kerja dan Efektifitas Komunikasi Organisasi dalam Meningkatkan Kinerja Karyawan - Abdilah; Asep Abdul Azij; Rustomo; Taryanto (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to determine whether there is an effect of work discipline and organizational communication on employee performance in Dharma Polymetal. The analytical method used in this research is descriptive quantitative analysis method. The sample in this study were employees of the Fastener Department with a total of 100 people or respondents. The sampling technique used was saturated sampling technique. The analytical tool used is factor analysis using IBM SPSS version 23. The results show that sequentially the factors that influence Work Discipline and Organizational Communication together on Employee Performance at Dharma Polimetal because the calculated F value (20.552) is greater than the F table value (3.090) so that H3 is accepted. Then Work Discipline and Organizational Communication together have a moderate positive effect (R value of 0.546) and have an influence contribution of 29.8% on the Employee Performance of Dharma Polimetal. While the remaining 70.2% is influenced by other factors. In addition, it is also known that the regression equation that can be used to predict the Employee Performance variable through the Work Discipline and Organizational Communication variables together is Y' = 15,437 + 0.425 X1 + 0.345 X2.